Cuiabá : cidade-narrativa - Mattos, Gabriel Francisco de (2019)
The basic principle of this thesis is that the city of Cuiabá, with its 300 years, is historical and simbolicaly defined on two apparently contradictory axes: Cuiabania and Modernidade. In order to observe and analyze them, I used the Theory of Structural Anthropology of the Imaginary of Gilbert Durand (1921-2012), through the aspects of the three layers (Pedagogical, Sage and Mass media), as well as the three regimes of images (diurnal, nocturnal and twilight), which propose to unravel the symbolic formation of a region at a given time. The aim is to unravel the troubled narrative of the city, invoking myth against myth (now modern, now conservative), looking for see the town constituting their imaginary constellations, at the junction of mythical narratives - in architectural monuments, buildings and literary discourses. Two analyses are made about the imaginary of Cuiabá. The first is made on the concept of Constellation of Images, basic stage to reach the Imaginary Anthropological Structures; here the conflict among the constellation of Cuiabania and the constellation of modernity. The second part is the concept of Semantic Basin or kaldounian trend, analysing a period of 150 years divided into six stages of creation and dissolution of the basin. The 300 years old history of the city enabled the discovery of classical director myths as Sisyphus and the Phoenix, in the first moment, evolving to the myths of modernity defined by Durand, Prometheus and Hermes, to which I have added two current myths, based on fictional cities: Nadrixerlinus (created by brazilian writer/poet Ferreira Gullar) and Wakanda (city of the comic book character Black Panther).